Successful Treatment of Incomplete Susac Syndrome with Simultaneous Corticosteroids and Plasmapheresis Followed by Rituximab - Mick B. Reedy; Yanping Wang; Brad R. Beinlich; William Nicholas Rose (Case Reports in Neurological Medicine)
We present a case report of a patient with incomplete Susac syndrome. He had cognitive impairment, corpus callosum lesions, and vestibulocochlear dysfunction on brainstem auditory evoked responses. He was treated with methylprednisolone and plasmapheresis, improved, and then, also received rituximab. His improvement has been lasting as of this writing. This case shares our experience with a successful treatment of this rare condition that is incompletely understood and lacks well-established treatment guidelines.